2015
DOI: 10.1038/ncomms9253
|View full text |Cite
|
Sign up to set email alerts
|

Coordination tuning of cobalt phosphates towards efficient water oxidation catalyst

Abstract: The development of efficient and stable water oxidation catalysts is necessary for the realization of practically viable water-splitting systems. Although extensive studies have focused on the metal-oxide catalysts, the effect of metal coordination on the catalytic ability remains still elusive. Here we select four cobalt-based phosphate catalysts with various cobalt- and phosphate-group coordination as a platform to better understand the catalytic activity of cobalt-based materials. Although they exhibit vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
293
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 383 publications
(315 citation statements)
references
References 71 publications
9
293
0
1
Order By: Relevance
“…Qi et al also reported the improved OER performance of Fe-doped NiO. [189] The Fe-doped NiO annealed up to 200 °C presented the highest catalytic efficiency with η = 487 mV at 62 mA cm −2 for Ni 85 Fe 15 .…”
Section: Rock-salt-type Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi et al also reported the improved OER performance of Fe-doped NiO. [189] The Fe-doped NiO annealed up to 200 °C presented the highest catalytic efficiency with η = 487 mV at 62 mA cm −2 for Ni 85 Fe 15 .…”
Section: Rock-salt-type Metal Oxidesmentioning
confidence: 99%
“…[4][5][6][7][8] However, the high cost of these scarce materials (Ru = $65 ozt −1 and Ir = $970 ozt −1 , Jul 2017) is a challenging obstacle for the largescale commercialization. [9][10][11] A number of studies have thus begun to focus on 3d-transition-metal-based catalysts, [12][13][14][15] with reports of high-efficiency catalysts such as amorphous Co-oxide, layered hydroxides, perovskites, and spinels. According to the works by Kanan and Nocera, an amorphous Co-oxide film catalyst was revealed to be an outstanding OER catalyst in neutral electrolytes, triggering extensive research on amorphous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Very recently, sodium metal phosphates NaCoPO 4 and Na 2 CoP 2 O 7 were studied as electrocatalyst for OER. [26] The Na 2 CoP 2 O 7 with distorted cobalt tetrahedral geometry exhibited enhanced activity and stability relative to cobalt phosphate. This report demonstrates that surface reorganization by the pyrophosphate ligand induces distorted cobalt tetrahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…This result favors binding of water molecules and it leads to low overpotential (~0.42 V) for water oxidation. [26] Particularly, polyanions affect the OER and ORR performance of the catalysts. [14,26,27] Recent report on OER catalytic performance of Mn 3 (PO 4 ) 2 in neutral solution showed the positive effect of polyanion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation